Actions aimed at reducing, reusing and recycling waste in the construction of buildings - Mata de Oliveira, Jaqueline; Lordsleem Júnior, Alberto Casado; de Gois Santos, Débora (National Journal of City Management, 2022)
Being responsible for the generation of more than 50% of urban solid waste poses incessant challenges to the construction industry. Commonly called rubble, civil construction waste (RCC) causes major environmental impacts when an order of priority of actions in forwarding the management of discarded materials is not observed. It is a situation that requires the application of practices that aim to reduce, reuse and recycle (3R's) the waste generated by civil construction at construction sites. This work aims to present good practice guidelines, through an action plan, for the reduction, reuse and recycling of RCC in construction sites. The methodology included a systematic review of scientific articles considering the indications of the PRISMA method (Preferred Reporting Items for Systematic reviews and Meta-Analyses). It also included a field research, with seven case studies, with five works located in the city of Recife and two works located in the city of Caruaru, both in the State of Pernambuco, in which we sought to investigate waste management in the works and the actions reduction, reuse and recycling carried out at construction sites. The results showed the identification of reduction actions applied to the management of services, materials and equipment used in the execution of works and good practices of reuse and recycling for the main construction materials, such as: concrete, wood, plastic, plaster and metal. The main contribution of this work was to identify and describe good practice guidelines for better management of civil construction waste in terms of the 3R's. KEYWORDS: Reduction. reuse. Recycling.